ChemInform Abstract: C—H Arylation and Alkenylation of Imidazoles by Nickel Catalysis: Solvent‐Accelerated Imidazole C—H Activation. Issue 11 (February 2016) - Muto, Kei; Hatakeyama, Taito; Yamaguchi, Junichiro; Itami, Kenichiro
Abstract: The first Ni‐catalyzed arylation of benzimidazoles (I) with aryl carbamates (II) leads to desired 2‐arylbenzimidazoles (III).